Acompanhamento clínico, histológico, histomorfométrico e radiográfico de biomateriais utilizados no tratamento na maxila posterior atrófica – ensaio clínico randomizado - Paiva, Luis Gustavo (2022)
Oral rehabilitation with osseointegrated dental implants can often be limited in situations of insufficient bone. Several techniques are described in order to restore an adequate amount of bone for the installation of dental implants. This research evaluate clinical, radiographic, histological and histomorphometric, the use of two bone substitute materials, Boneceramic and Bio-Oss, or the clot, in maxillary sinus lift procedures. 36 maxillary sinuses were operated. For the first objective Computed tomography scans were performed, in blood clot group, preoperatively and 6 months postoperatively in order to measure bone height and volume in both periods. We demonstrated a satisfactory gain in height, area and volume for rehabilitation with osseointegrated dental implants. The second and third objectives were to evaluate and compare histomorphometrically and histologically the newly formed bone with two different biomaterials, one xenogenous (BioOss) and one synthetic (BoneCeramic), in addition to not using biomaterials. We demonstrated a similarity in the percentage of newly formed bone.